'I have my everything in here': Welcome, unwelcome and rewelcome in asylum seeker's deportability. Issue 2 (1st June 2022) - Lyytinen, Eveliina
In this article, I analyse the intertwined concepts of hospitality and welcome and their negatives in the context of seeking asylum and deportation. I focus on the scales of individual and community welcome, but also reflect on welcome at the state level. The analysis considers the case of Zaki, a young Afghan man who migrated to Finland in 2015. Zaki experienced welcome, unwelcome and rewelcome in four different stages of migration: his arrival in Finland as an unaccompanied minor, going through the asylum process as an adult man, being deported to Afghanistan and re-entering Finland with an employment-related immigration status. These analytical stages provide a unique opportunity to both consider the politics of welcoming people at different scales and to repopulate the abstract discussions about welcome and hospitality. My analysis is focused on Zaki's and his Finnish friends' narration of hospitality and welcome during these four stages. The data used in the article includes interviews with Zaki and four local Finns with reference to deportation statistics, asylum policies and media coverage. This article answers the recent call to examine the lived experiences and perspectives of deportees and their communities and also to recentre the individual within the analysis of welcome.